SELECTIVE MEDIA FOR THE ISOLATION OF PASTEURELLA PESTIS - Knisely, Ralph F. (1964)
Knisely, Ralph F. (U.S. Army Biological Laboratories, Fort Detrick, Frederick, Md.), Lois M. Swaney, and Harold Friedlander. Selective media for the isolation of Pasteurella pestis. J. Bacteriol. 88:491–496. 1964.—Several selective media are described that were successfully used to isolate virulent and avirulent strains of Pasteurella pestis from material heavily contaminated with other organisms. These media are comparatively easy to prepare, consist of readily available ingredients, and usually require no adjustment of the pH. One of the selective media described permits excellent recovery and the growth of large, easily distinguishable colonies of P. pestis in 48 hr at 26 C, and also allows the detection of fewer numbers of P. pestis organisms in soil than a previously recommended selective medium. The inhibition of other organisms frequently present in clinical specimens is described.